RESEARCH TRENDS IN CREATIVE ACCOUNTING AND EARNINGS MANAGEMENT: A GLOBAL BIBLIOMETRIC ANALYSIS (1996–2025) - Sartika, Dewi; Rahmi, Fitria; Mulyani, Fitrah; Dahar, Reni (Jurnal Cakrawala Akuntansi, 2026)
In modern accounting literature, creative accounting and earnings management have attracted growing attention due to their significant implications for the credibility and reliability of financial statements. This study systematically examines global research trends on these phenomena using a bibliometric approach based on 46 Scopus-indexed articles published between 1996 and 2025. By employing VOSviewer and Biblioshiny, the analysis maps publication performance as well as the intellectual, conceptual, and collaborative structures of the field. The results indicate that research on creative accounting and earnings management is predominantly driven by contributions from the United States, the United Kingdom, and Spain, with leading institutional output from the University of Salamanca. Co-citation, co-authorship, and keyword co-occurrence analyses identify three dominant thematic domains: governance and ethics, financial behaviour and accrual manipulation, and institutional context and earnings quality. The novelty of this study lies in integrating creative accounting and earnings management within a single bibliometric framework, providing a holistic perspective on how these closely related topics intersect with emerging issues such as ESG disclosure, sustainability reporting, and digital-based financial transparency. The findings reveal an intellectual shift from a predominantly technical focus on earnings manipulation toward a broader, multidisciplinary perspective that incorporates corporate governance, ethical considerations, and sustainability. The results offer theoretical implications by extending the relevance of agency, legitimacy, and stakeholder theories in contemporary financial reporting ethics, and practical implications for regulators, auditors, and policymakers aiming to enhance transparency, cross-country collaboration, and sustainability-oriented governance mechanisms.